Failure of Laminated Fibre-reinforced Composite Structures Subject to Combined Loadings - Nahas, Mahmoud Nadim (Cranfield University, 1980)
A new modified maximum strain failure criterion is proposed to predict the failure of the laminae of laminated fibre-reinforced composite structures when the laminate is subjected to combined loadings. The new criterion takes into account the layer non-linear behaviour which is an important factor in the failure prediction operation. The analysis of laminated structures containing laminae with non-linear stress-strain response is also studied and a new method is proposed for this analysis. The modified failure criterion introduces two levels of failure. The lower level is associated with the “yield” of the lamina, or the beginning of the lamina degradation, above which the lamina will exhibit irreversible damage. The higher failure level however, is associated with the “ultimate” failure of the lamina, above which the lamina cannot sustain any load. Cont/d.

A new modified maximum strain failure criterion is proposed to predict the failure of the laminae of laminated fibre-reinforced composite structures when the laminate is subjected to combined loadings. The new criterion takes into account the layer non-linear behaviour which is an important factor in the failure prediction operation. The analysis of laminated structures containing laminae with non-linear stress-strain response is also studied and a new method is proposed for this analysis. The modified failure criterion introduces two levels of failure. The lower level is of the lamina degradation, above which the lamina will exhibit irreversible damage. The higher failure level, however, is associated with the “ultimate” failure of the lamina, above which the lamina cannot sustain any load. After the “ultimate” failure of a lamina in a certain direction, the post-failure model proposed in this study assumes the failed layer to unload in the failed direction only following a decreasing exponential function where the secant modulus decreases gradually to zero. The theoretical results are compared with experimental results obtained from tests carried out on tubular composite specimens under combined loading conditions. Acoustic emission, C-scanning and photomicrographic tests were also conducted to examine the damage caused when the linear limit is exceeded. The cylindrical specimens used in the experimental investigation introduced two additional problems which are also studied here. These are the design of the tubular test specimens, and the buckling of cylindrical shells under combined loading. Comprehensive survey of the previous theories for all the problems studied in this thesis is presented, and where possible, the results obtained by previous investigators are compared with the present proposed solutions and commented on.